Systematic review of hepatic arterial infusion chemotherapy versus sorafenib in patients with hepatocellular carcinoma with portal vein tumor thrombosis. Issue 8 (3rd March 2020) - Liu, Miao; Shi, Junyi; Mou, Tong; Wang, Yang; Wu, Zhongjun; Shen, Ai
Abstract: Background and Aim: The prognosis of hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) is very poor. This study aimed to evaluate hepatic arterial infusion chemotherapy (HAIC) versus sorafenib (SORF) in the treatment of HCC with PVTT. Methods: Studies were identified online in Embase and MEDLINE before October 31, 2019. The end‐points were overall survival (OS), progression‐free survival (PFS), disease control rate (DCR), and safety. Results: Six studies with 417 cases were included in this systematic review. Meta‐analyses demonstrated that HAIC is superior to SORF with respect to OS (hazard ratio [HR]: 0.50, 95% confidence interval: 0.38–0.66, P  < 0.001) and PFS (HR: 0.47, 95% confidence interval: 0.31–0.73, P  = 0.001) irrespective of research territoriality and study quality. Our systematic review also demonstrated that HAIC is superior to SORF with respect to DCR. Subgroup analysis demonstrated that the advantage is more obvious in the treatment of types III–IV PVTT with respect to OS (HR: 0.29, P  < 0.001) and PFS(HR: 0.39, P  < 0.001). HAIC caused more grades 3–4 neutropenia (HR: 10.71), anemia (HR: 7.55), leukopenia (HR: 10.38), and thrombocytopenia (HR: 13.09) than SORF. However, HAIC caused fewer cases of grades 3–4 aspartate aminotransferase rising (HR: 0.21), diarrhea (HR: 0.14), and hand‐foot syndrome (HR: 0.14) than SORF. Conclusions: This systematic review demonstrated that HAIC is superior to SORF in HCC with PVTT with respect to OS, PFS, and DCR, especially in HCC with types III–IV PVTT. HAIC caused more myelosuppression, whereas SORF is associated with diarrhea and hand‐foot syndrome. Further randomized controlled trials are warranted.